Effect of AIUEO Vocal Therapy in Non-Hemorrhagic Stroke Patients with Verbal Communication Disorders: A Case Report - Intan Nur Annisa; Rondhianto; Ana Nistiandani; Mohammad Shodikin (KHD Production, 2024)
Stroke is a disease that is a health problem throughout the world. Stroke can cause long-term damage to nerve function or brain damage, long-term disability, and even death. Stroke can cause sufferers to experience weakness due to damage to nerve function. If a stroke attacks the left brain and hits the speech center, it is likely that the patient will experience speech disorders or verbal communication disorders. One form of rehabilitation therapy to correct verbal communication disorders in someone who suffers from verbal communication disorders is